PERAN KOMPETENSI GURU PERAN KOMPETENSI GURU DALAM MENGEMBANGKAN KARAKTER DISIPLIN MELALUI PEMBIASAAN DI RA KHOIRIYAH GUWO TLOGOWUNGU PATI: Kompetensi Guru dalam Mengembangkan Karakter Disiplin melalui Pembiasaan - Ulfah Hidayati (Liberi, 2023)
Abstract This paper discusses how teacher competence develops students' disciplinary character through habituation at RA Khoiriyah Guwo Tlogowungu Pati which uses four competencies including professional competence, pedagogic competence, personal competence, and social competence. The results of competence in developing disciplinary character through habituation can be seen from changes in attitudes and behavior experienced by students, teachers are able to choose learning and disciplinary character methods that are appropriate to the level of development, habituation of a clean environment and carry out 5S habituation (smile, greeting, greeting , polite and courteous), as well as the cooperative relationship between teachers and parents in forming relationships for monitoring students. Keywords: Teacher Competence, Discipline Character, Habituation